PENERAPAN METODE CERTAINTY FACTOR DALAM MENENTUKAN MAKANAN YANG DIKONSUMSI BERDASARKAN KONDISI DAN KEBUTUHAN STANDAR TUBUH MANUSIA - Haris, Abdul (PETIR, 2015)
It has been long to known that food plays an important role in efforts to prevent and cure diseases, to develop the human resources potential, achieve a better quality and achieve longer life as well. It is proper nutrition issues into the affairs of all of us, both at the individual, household, and national levels. In a healthy or unhealthy condition, food needs to be regulated well. Because of shortage and excess nutrients will cause the body disease. This occurs because of an error in dietary habit and a lack of understanding and knowledge of proper nutrition. This is the reason that author wants to make an application on nutrition with method certainty factor. So users have a better knowledge about nutrition. Desktop application created with Visual Basic .NET using Oracle Database.